HUBUNGAN BENTUK TELAPAK KAKI FLAT FEET DENGAN VO2 MAKS PADA ATLET PENCAK SILAT TINGKAT PROVINSI DKI JAKARTA BERDASARKAN LAMA LATIHAN - Dhia Adhi Perwirawati; Nurfitri Bustamam; Basuki Supartono; Ayodya Heristyorini (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Flat feet can cause a reduction in the foot function resulting in fatigue when walking or running. This condition can result in a suboptimal intensity exercise required to improve VO2Max of Pencak Silat athletes. This study aimed to determine the relationship between the shape of foot and VO2Max based on training duration among Pencak Silat athletes at the provincial level of DKI Jakarta. The study used a cross-sectional design involving 46 athletes selected through a total sampling. The subject criteria for this study included athletes aged 17-24 years, healthy, and had no lower extremities problems. The study utilized footprint test and multistage fitness test instruments. The study found that 27 (58.7%) athletes had a normal foot shape, while 19 (41.3%) had flat feet. There were no differences in age, sex, body mass index, and training duration between the two groups of foot shape (p 0.05). The maximum VO2 value was 45.0 (7.2) ml/kg/min in athletes with normal foot shape and 40.1 (70.5) ml/kg/min in athletes with flat feet. The independent t-test revealed a significant difference in VO2Max between the two groups of foot shapes (p = 0.028). The increase of VO2Max was in line with the duration of exercise, but this increase was not significant in subjects with flat feet compared to those with normal foot shape. It concludes that flat feet are negatively associated with VO2Max of athletes.  Pencak Silat athletes with flat feet must exert extra effort to enhance their VO2Max, such as interval training and kinesio taping. Further research is recommended to explore the impact of these efforts on improving VO2Max.